Seismic Response Analysis of Masonry Minaret and Possible Strengthening by Fiber Reinforced Cementitious Matrix (FRCM) Materials - TÜRK, AHMET MURAT (Hindawi Publishing Corporation, 410 Park Avenue, 15Th Floor, #287 Pmb, New York, Ny 10022 Usa, 2013)
This paper presents the analytical study on the dynamic response of a natural stone block masonry minaret of a historical mosque located in Istanbul, Turkey. A three-dimensional finite element model of the whole minaret, adjusted with former in situ ambient vibration test results, was used in order to get probable lateral displacements, stresses, and understanding of failure modes under seismic loading. Particularly, FEM has been used to evaluate the seismic safety of the minaret in present-day condition and after the application of a proposed strengthening method. In this method, by utilizing the fiber reinforced cementitious matrix (FRCM) material, the critical cross-sections were jacketed. The appearing damage for the bare minaret obtained from FEM analyses was located at the boot and transition part of the minaret. After FRCM material was wrapped around these critical cross-sections, the analytical results indicated that such method appears effective in terms of the seismic response. It also appears less invasive in terms of the conservation of historical heritage like minarets without causing aesthetic conflict on the existing structure when compared to other available techniques.
Keywords: Dynamic-Response; Concrete; Dinemik tepki; Beton